Występowanie i nasilenie distresu u pacjentów z nowotworem złośliwym w okresie przygotowania do leczenia chirurgicznego = The occurrence and severity of distress in cancer patients during preparation for surgery - Marta Łuczyk; Katarzyna Śniszewska; Robert Łuczyk; Agata Pietraszek; Agnieszka Bartoszek; Katarzyna Kocka; Zdzisława Szadowska-Szlachetka (Kazimierz Wielki University, 2016)
Łuczyk Marta, Śniszewska Katarzyna, Łuczyk Robert, Pietraszek Agata, Bartoszek Agnieszka, Kocka Katarzyna, Szadowska‑Szlachetka Zdzisława. Występowanie i nasilenie distresu u pacjentów z nowotworem złośliwym w okresie przygotowania do leczenia chirurgicznego = The occurrence and severity of distress in cancer patients during preparation for surgery. Journal of Education, Health and Sport. 2016;6(7):498-512. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.58776 http://ojs.ukw.edu.pl/index.php/johs/article/view/3713       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.06.2016. Revised 15.07.2016. Accepted: 26.07.2016.     Występowanie i nasilenie distresu u pacjentów z nowotworem złośliwym w okresie przygotowania do leczenia chirurgicznego The occurrence and severity of distress in cancer patients during preparation for surgery   Marta Łuczyk1, Katarzyna Śniszewska2, Robert Łuczyk3, Agata Pietraszek1, Agnieszka Bartoszek4, Katarzyna Kocka4, Zdzisława Szadowska-Szlachetka1   1Zakład Onkologii, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 2 Absolwentka Wydziału Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 3 Katedra Interny z Zakładem Pielęgniarstwa Internistycznego, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 4 Zakład Medycyny Rodzinnej i Pielęgniarstwa Środowiskowego, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie       Streszczenie Wstęp. Pacjent z rozpoznanym nowotworem złośliwym, który oczekuje na zabieg operacyjny odczuwa różnego rodzaje emocje. Jedną z nich jest distres będący reakcją na zagrożenie związaną z diagnozą zagrażającej życiu choroby oraz koniecznością jej leczenia. Jeżeli distres przekracza możliwości adaptacyjne ustroju może działać szkodliwie na organizm [1].   Cel pracy. Ocena występowania i nasilenia distresu u chorych na nowotwory złośliwe w okresie przygotowania do zabiegu chirurgicznego. Materiał i metoda. Badaniem objęto 101 osób z rozpoznanym nowotworem złośliwym zakwalifikowanych do leczenia chirurgicznego. Do badań wykorzystano autorski kwestionariusz wywiadu oraz Termometr distresu. Wyniki. U ponad połowy pacjentów z rozpoznanym nowotworem złośliwym w okresie przygotowania do zabiegu chirurgicznego występowało niewielkie nasilenie distresu, u części chorych nasilenie distresu było znaczne. U pacjentów z nasilonym poziomem distresu najczęściej wskazywanymi problemami były trudności w pracy i szkole, w relacjach z partnerem oraz poddenerwowanie i zmęczenie. Na występowanie i nasilenie distresu u pacjentów onkologicznych przygotowywanych do zabiegu chirurgicznego nie mają wpływu czynniki społeczno-demograficzne oraz rodzaj rozpoznanego nowotworu.   Słowa kluczowe: nowotwór złośliwy, distres, termometr distresu, leczenie chirurgiczne nowotworów.       Summary Admission. A patient diagnosed with a malignant tumor that is pending surgery feels different kinds of emotions. One of them is the distress that is a reaction to the threat associated with the diagnosis of a life-threatening disease and the need for its treatment. If the distress exceeds the capabilities of the adaptive system can cause harm to the body [1]. Aim of the study. To estimate the prevalence and severity of distress in cancer patients during preparation for surgery. Material and methods. The study involved 101 people diagnosed with a malignant tumor qualified for surgical treatment. The study used an original interview questionnaire and the distress thermometer. Results. More than half of patients diagnosed with malignant the period of preparation for surgery occurred mild distress, in some patients the severity of distress was considerable. In patients with severe levels of distress following most common problems were difficulties at work and school, in the relationship with a partner, and usually follows, and fatigue. The occurrence and severity of distress in cancer patients before surgery do not affect the socio-demographic factors and the type of cancer diagnosed.   Keywords: cancer, distress, distress thermometer, surgical treatment of cancer.